Serosurvey of Bovine Viral Diarrhea Virus in Cattle in Southern Japan and Estimation of Its Transmissibility by Transient Infection in Nonvaccinated Cattle - Norikazu Isoda; Satoshi Sekiguchi; Chika Ryu; Kosuke Notsu; Maya Kobayashi; Karin Hamaguchi; Takahiro Hiono; Yuichi Ushitani; Yoshihiro Sakoda (Viruses)
Bovine viral diarrhea (BVD) is caused by the BVD virus (BVDV) and has been reported worldwide in cattle. To estimate BVDV circulation among cattle where few BVD cases were reported in southern Japan, 1910 serum samples collected from 35 cattle farms without a BVD outbreak were investigated to detect antibodies against BVDV-1 and BVDV-2 using an indicator virus with a cytopathogenic effect and the luciferase gene, respectively. Neutralizing antibodies against BVDV-1 and BVDV-2 were detected more frequently in 18 vaccinated farms than in 17 nonvaccinated farms. In the nonvaccinated farms, 9.6%, 1.8%, and 13.8% of the cattle were estimated to have a history of infection with BVDV-1, BVDV-2, and both, respectively. The median rate of within-herd anti-BVDV-1 seropositivity among cattle in the nonvaccinated farms was 22.0%; however, a high within-herd seropositivity (>50%) was confirmed in the two farms. The force of infection, basic reproduction number, and annual probability of BVDV-1 infection were estimated as 0.072 (95% confidence interval [CI]: 0.062–0.084), 0.36 (95% CI: 0.31–0.42), and 0.73% (95% CI: 0.61–0.87%), respectively, using the age-specific positive rate of anti-BVDV-1 antibodies. These parameters should be further applicable for developing epidemiological models which illustrate the BVDV dynamics in the field.